The AIDS pandemic : complacency, injustice, and unfulfilled expectations - Gostin, Lawrence O. (Lawrence Ogalthorpe) (Studies in social medicine., 2004)
In this collection of essays, Lawrence O. Gostin confronts the pressing and controversial issues surrounding AIDS in America and around the world. He shows how HIV/AIDS affects the entire US population - infected and uninfected - by influencing its social norms, economy, and the country's role.